Effects of quercetin on oral administration of cannabinol and alcohol on reproductive functions in male Wistar rats (2019)
The male reproductive system ensures the continuity of species; however, several toxicants have demonstrated hampering effects on the structures of male reproductive system, thereby leading to reduced physiological functions. This study was carried out to investigate the effect of quercetin in experimental rats treated with alcohol and/or cannabinol. Forty-five male rats were grouped into the following: Group 1 rats were given distilled water. Group 2 rats were administered with methanol. Group 3 rats were administered with alcohol (3g/kg bw as 25%v/v). Group 4 rats were administered with cannabinol (10mg/kg bw). Group 5 rats were administered with cannabinol (10mg/kg bw) and alcohol (3g/kg bw as 25%v/v). Group 6 rats were administered with quercetin (30mg/kg bw). Group 7 rats were administered with alcohol (3g/kg bw as 25%v/v) and quercetin (30mg/kg bw). Group 8 rats were administered with cannabinol (10mg/kg bw) and quercetin (30mg/kg bw). Group 9 rats were administered with cannabinol (10mg/kg bw) plus alcohol (3g/kg bw as 25%v/v) plus quercetin (30mg/kg bw). At the end of the experiment, animals were sacrificed and their reproductive organs were harvested and weighed immediately. Results showed that rats treated with alcohol and/or cannabinol had significant decrease (p<0.05) in sperm indices, lipid peroxidation, gonadotrophic hormones and male sex hormone (testosterone); however, with quercetin co-treatment with alcohol and/or cannabinol administration the results obtained in the reproductive parameters showed ameliorative potential of quercetin in the present study.